MODEL KOMUNIKASI DAN PERSEPSI PUBLIK DALAM PENATAAN DESA DI BIDANG PENATAAN DESA DAN PEMERINTAHAN DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN BANYUMAS - Gian Widayoko; Sugeng Dwi Harianto; Enung Asmaya (STKIP Subang, 2026)
Public perception of village restructuring policies constitutes a crucial factor in determining the success of policy implementation. Perception is shaped not only by the substance of the message delivered, but also by the mode of delivery, the credibility of the communicator, and the prior experiences of the community. This study employs a qualitative research approach. The findings indicate that the success of village restructuring policies is largely determined by the effectiveness of organizational communication models, the appropriateness of governmental communication strategies, and the ways in which public perception is constructed within society. A structured and well-coordinated communication model within the Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Banyumas serves as a fundamental foundation in maintaining message consistency and policy synchronization prior to dissemination to the public. Communication strategies emphasizing transparency, participation, dialogue, and the involvement of community leaders have proven effective in enhancing public trust and support for the implemented policies. Furthermore, public perception is influenced by prior experiences, levels of informational understanding, socio-economic conditions, and the dynamics of local cultural contexts within villages. Therefore, adaptive, inclusive, and sustainable communication is essential in building social legitimacy and ensuring that village restructuring policies are accepted and effectively implemented, ultimately contributing to accountable and sustainable village governance in Banyumas Regency. Keywords: Communication; Public Perception; Village Restructuring Policy; Government